Emoções e lembranças associadas ao consumo de café em ambientes evocados via internet - Mequelino, Daiana Barbosa (2022)
The growing demand for qualified coffees shows the need to use techniques that allow obtaining a robust characterization of the product and consumers. Methodological innovations in sensory sciences are important for improving product quality. In this way, a new research methodology was proposed via the internet, in evoked environments, to analyze the acceptability of coffee. To optimize the consumer experience, a lexicon specialized in memories elicited by coffee consumption was developed and the lexicon of emotions was refined, through the CATA methodology. Given the above, this work has the main objective of answering how different environments evoked via the internet affect the acceptance of the coffee drink, and what are the main emotions and memories associated with its consumption in these environments. An online survey was carried out and the data obtained were evaluated using exploratory analysis, through descriptive statistics and sensorometric analysis, such as: analysis of variance (ANOVA), Scott-Knott test, correspondence analysis and chi-square test. The survey was answered by Brazilians, aged between 18 and 67 years, with a prevalence of female participants. The results point to a higher rate of acceptability of coffee when consumed in the kitchen and cafeteria evoked via the internet, while the laboratory and the supermarket were the least accepted environments. The study enabled the development of a memory lexicon composed of 17 terms and selected 28 emotional terms for coffee consumption. It was observed that consumers tend to associate coffee consumption in environments evoked via the internet, with pleasant memories and emotions. Indicating that the motivations for its consumption reflect a satisfactory social meaning of the drink.